Disaster Management for Children Protection - Sugiyanto, Sugiyanto; Musoli, Musoli (International Journal of Engineering and Technology, 2026)
Recognizing Indonesia as a country prone to disasters and the potential to reduce the risk necessary preventive measures for all citizens, including children living in disaster-prone areas. There are the most high vulnerable disasters to children in times of disaster victims in Indonesia. A child is someone having no 18 years old yet; including those still having in the mothers’ womb and those unmarried ones. The United National Treaty, a Convention on the Right of Children Retrieved 2009 every child has the seven rights, one of which is that to the fulfillment of all requirements including safety needs of the disaster and rights protection. On the other side of the Convention on the rights of children, it must uphold the rights of children and the survival of the principle of non-discrimination.Disaster management of child protection in this article is a concept of planning and maket which are easily applied consisting of: 1) preventive planning by describing the potential environmental hazard; the potential for serious harm to the child who starts from the learning to the prevention, giving the preparedness of the child in facing catastrophic events, Management of mitigation is readily accepted by the children and can be done or undertaken by the organized children with the plot to the prevention, preparedness and emergency response of each child, Recovery and rehabilitation of children at all age levels with a variety of directions to minimize the crisis they encounter are realized within the framework of post-disaster rehabilitation and reconstruction easily to do, fun without any pressure. This article is devoted to the children under normal conditions, meaning that any knowledge, experience and skills contained in this article do not apply to children with special needs.
Keywords: Management Disaster; Child Protection